2022
DOI: 10.1186/s12902-022-01069-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI-negative Cushing’s Disease: Management Strategy and Outcomes in 15 Cases Utilizing a Pure Endoscopic Endonasal Approach

Abstract: Background Cushing’s disease (CD) is among the most common etiologies of hypercortisolism. Magnetic resonance imaging (MRI) is often utilized in the diagnosis of CD, however, up to 64% of adrenocorticotropic hormone (ACTH)-producing pituitary microadenomas are undetectable on MRI. We report 15 cases of MRI negative CD who underwent surgical resection utilizing a purely endoscopic endonasal approach. Methods Endoscopic endonasal transsphenoidal surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…In the series presented by Sharifi et al [ 35 ] and some other series [ 8 , 12 , 32 , 36 ], no significant difference was observed between the remission rates of CD cases with and without a conclusive MRI.This finding is controversial since other studies showed decreased remission rates with preoperative inconclusive MRIs [ 13 , 40 ]. Similar to the results reported by Sharifi et al [ 35 ], we did not find a statistically significant difference between the remission rates of tumors <6 mm and those between 6–20 mm. However, a significant difference was observed between tumors <6 mm and those ≥20 mm.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the series presented by Sharifi et al [ 35 ] and some other series [ 8 , 12 , 32 , 36 ], no significant difference was observed between the remission rates of CD cases with and without a conclusive MRI.This finding is controversial since other studies showed decreased remission rates with preoperative inconclusive MRIs [ 13 , 40 ]. Similar to the results reported by Sharifi et al [ 35 ], we did not find a statistically significant difference between the remission rates of tumors <6 mm and those between 6–20 mm. However, a significant difference was observed between tumors <6 mm and those ≥20 mm.…”
Section: Discussionmentioning
confidence: 95%
“…In our series, when the tumors were stratified further by the tumor size, the medium-term remission rate further decreased to 36% for tumors ≥20 mm in size, although the remission rates for other groups <20 mm were all above 75% ( p =0.003). Sharifi et al [ 35 ] classified pituitary MRI scans in CD showing a tumor size <6 mm as “inconclusive” because incidentalomas are frequent among tumors in this size range, and this size is not indicative of CD. Previously published series reported that the rate of inconclusive MRI scans in CD was 36–64%, and the remission rates varied between 50% and 71% for those with an inconclusive MRI scan [ 10 , 24 , 27 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach differs from conventional resection of pituitary adenomas visible on MRI, as emphasis is placed on the exploration of the pituitary gland and the cavernous sinus while preserving as much of the normal gland as possible. 1 …”
Section: Transcriptmentioning
confidence: 99%
“…1 However, the surgical approach to MRI-negative CD presents significant challenges, given that many CDs exhibit no visible tumor despite the advancements in pituitary imaging. 2-6 This leads to the decision to undertake surgery in MRI-negative CD remaining a contentious issue. Furthermore, the rare manifestation of double pituitary tumors is predominantly associated with adrenocorticotropic hormone (ACTH)–secreting or growth hormone–secreting tumors.…”
mentioning
confidence: 99%